MANAGEMENT DIVERSITY AND CORPORATE SOCIAL RESPONSIBILITY OF QUOTED FIRMS IN NIGERIA - Adedeji Daniel Gbadebo (J-MACC, 2025)
In recent years corporate social responsibility has become a major focus of interest for policymakers, regulators, and academics. Corporate social responsibility (CSR) is basically a concept of voluntary business activities whereby corporations integrate social concerns and other environmental concerns into their economic activities. The study hinged on stakeholder theory to serve as the main theoretical framework. Pool OLS with tests for fixed and random effects was employed to estimate the impact of board diversity, and CSR. The study employs the Generalized Least Square (random effects) regression to examine how board diversity components, including nationality, educational qualifications and gender, affect CSR of 20 listed industrial and commercial goods on the Nigerian Exchange Group, during 2015-2019. The result shows that it is only gender diversity that has a significant positive relationship with corporate social responsibility expenditure while foreign nationality and educational diversity have revealed no significant effect on corporate social responsibility expenditures. This result is revealing that an increase in female representation in the boardroom will result in a corresponding increase in CSR expenditures of companies. This result confirms that women directors might take CSR issues more seriously than their male counterparts not only because of their stronger moral orientations.